PEMANFAATAN MESIN PENCACAH JANGGEL JAGUNG SEBAGAI CAMPURAN NUTRISI PAKAN TERNAK KAMBING RUMINANSIA DI KELURAHAN SUMBEREJO: PEMANFAATAN MESIN PENCACAH JANGGEL JAGUNG SEBAGAI CAMPURAN NUTRISI PAKAN TERNAK KAMBING RUMINANSIA DI KELURAHAN SUMBEREJO - anggra fiveriati; Anis Usfah; Abdul Rohman (Universitas Negeri Surabaya, 2022)
Goat farming is one type of work that the majority of Banyuwangi residents do. The economic value of raising goats is quite high. However, its development in caring for livestock has experienced difficulties due to high feed costs and reduced grass or leaf limitations. This impact causes the feed supply to livestock to decrease; with this impact, farmers have to allocate time to forage for livestock (Ramban/ruminants) by taking green plants, so it is very inefficient for today's society. There must be innovations to replace mandatory feed (Ramban) with alternative feeds to overcome the dependence on a feed from browsers. In the stage of this community service activity, starting from the initial stage, namely, the service team designed a corn cob chopper, in the second stage, the service team held socialization on the utilization of corn cob waste as a basic ingredient for animal feed by using silage, the next stage was training on the operation and maintenance of the corn cob chopper. Followed by training in the manufacture of animal feed, and at the last stage, the service team held regular monitoring to ensure partners could use the corn cob chopper and make good animal feed. The benefits of this service activity are aimed at increasing the amount of animal feed production to meet the feed of the members of the farmer group. In addition, in one manufacturing process, it can meet animal feed for the next few days.